Keys for writers : a brief handbook - Raimes, Ann. (Houghton Mifflin, 1999)
The writing process. Doing research. MLA documentation. APA, CBE, and Chicago documentation. Special writing situations: college, career, and online. The 5 C's of style and sentence review...